How does a solitary bee find its nest? A case study with the solitary bee Centris (Heterocentris) analis (Fabricius) (Hymenoptera, Apidae, Centridini) - Antunes, Pedro Reis (2019)
The knowledge of the sensory and cognitive capacity of insects is, mostly, restricted to studies with social species. However, more than 85% of bees are solitary. Using the bee Centris (Heterocentris) analis (Fabricius) as a model, we aimed to understand which information (spatial or visual), this tropical solitary bee mostly relies on in the context of nest recognition. Using a homogeneous background, we evaluated the effect of continuous and varied nest position in the presence and absence of coloured stimuli, and the possible effect of colour (blue or green) and training on accuracy and search time of returning females. Bees were able to adapt to new cues to find their nests, but performance varied among treatments. Our results have shown that besides spatial information, bees can use the presence of a coloured stimulus to enhance the accuracy during nest location, and that odour is a secondary cue in this process. Overall, as females gained experience with a task, they would require more time before making a choice, a result that seems to be modulated by treatments associated with the presence of visual stimuli.